Prevalence of age Related Macular Degeneration in A Tertiary Care centre - Jayashree MP; Harika JVL; Arathi C; Brijesh A Patil; Niveditha RK (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2019)
Background: Age-related macular degeneration (AMD) is one of the leading cause of irreversible blindness in elderly population affecting the quality of life and there by general health. AIM: The purpose of the present study was to estimate the prevalence, risk factors and subtypes of AMD in a hospital population attending to ophthalmology outpatient department. Materials and Methods: This observational study was carried out at tertiary eye institute between November 2017 and April 2018. Newly registered patients of both the sex attending the hospital with complaints of diminution of vision for various reasons were selected for detailed ophthalmic examination and evaluation.  Results: Among the patients attending to our outpatient department, 120 patients were diagnosed with Age related macular degeneration. As the age of subjects increased prevalence also increased and most of them were in the age group of 61-70. Male to female ratio was 1:2.33. Early AMD was seen in 71.7% (n = 86) and Late AMD (n= 34) was seen in 28.3%. Dry AMD was seen in 75.84% (n=91), Wet AMD was seen in 24.16% (n=29).  Conclusion: Study reports prevalence of AMD increases with age. Higher prevalence was noted in females. Early AMD was seen in more cases than Late AMD and Dry AMD was noted more than Wet AMD. So complete ophthalmic evaluation is necessary in order to diagnose and stabilize the progression of AMD especially in the elderly age group of patients who complains of recent onset central visual loss.